Pecularities of collaboration during first soviet occupation - Truska, Liudas (Genocidas ir rezistencija, 2025)
The specificity of collaboration in 1940 is its mass scale: collaboration had penetrated all segments of the population that was living in social illusions. The consequences of the collaboration were very painful; the occupiers succeeded in creating the appearance of Lithuania’s voluntary and legitimate entry into the USSR. The author analyses the attitudes of social groups within the context of the concept of collaboration during the Soviet occupation.
Keywords: Soviet occupation; colaboration; intelegentsia; Catholic Church; communist party